Mini review on the preservatives for Natural Rubber Latex (NRL) - Adhikari, A. M. K. S. P.; Abdul Rahman, N.; Ismail, M. F.; Zainuddin, N. (Malaysian Institute of Chemistry, 2023)
Natural rubber latex (NRL) harvested from the Hevea Brasiliense tree contains colloidal rubber particles, carbohydrates, and various plant proteins. The non-rubber substances in NRL lead to spontaneous coagulation that cause the rubber to rot within 3-5 hours. Many chemicals are used for the preservation of NRL to suppress spontaneous coagulation and putrefaction and improve the stability of the latex for long-term storage. Ammonia (NH3) is the most commonly used and most effective preservative of NRL. However, it has the potential to cause health problems. Recently several naturally occurring substances, synthetic chemicals, and nanomaterials have been introduced to NRL for preservation purposes. These preservatives are reviewed and their advantages and disadvantages are summarized in this mini-review.